2006
DOI: 10.2134/agronj2005-0012
|View full text |Cite
|
Sign up to set email alerts
|

Forage Chicory and Plantain Nutritive Value of Herbage at Variable Grazing Frequencies and Intensities

Abstract: Cultivars of forage chicory (Cichorium intybus L.) and plantain (Plantago lanceolata L.) grown in the northeastern USA have acceptable seasonal productivity; however, their reproductive habit could limit herbage nutritive value. The nutritive value of chicory and plantain cultivars was compared and examined under the effect of variable frequency and intensity of grazing. The cultivars were compared with 'Pennlate' orchardgrass (Dactylis glomerata L.), a productive grass during the summer, in two grazing experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Labreveux et al . () reported similar findings , with lower in vitro digestibility in plantain swards compared with chicory and forage grasses in grazing experiments. However, the higher HA of plantain swards may counter this in terms of the likely milk production response.…”
Section: Discussionsupporting
confidence: 62%
“…Labreveux et al . () reported similar findings , with lower in vitro digestibility in plantain swards compared with chicory and forage grasses in grazing experiments. However, the higher HA of plantain swards may counter this in terms of the likely milk production response.…”
Section: Discussionsupporting
confidence: 62%
“…Sulas (2004) reported that ADF content of chicory ranged from 25.8-49.9%. Labreveux et al (2006) reported that NDF content of chicory ranged from 25.5-39.9%.…”
Section: Resultsmentioning
confidence: 99%
“…Sanderson et al (2003b) reported that Forage Feast chicory had 20% higher CP than Lacerta chicory, and slightly higher CP than Puna chicory. While evaluating chicory cultivars in a grazing experiment, Labreveux, Sanderson, and Hall (2006) noted that the average CP of cultivars varied from 180-200 g kg −1 . Also, CP content of chicory at the vegetative growth stage averaged 187 g kg −1 in studies by Crush and Evans (1990), 222 g kg −1 by Niezen et al (1993), 183 g kg −1 by Volesky (1996), and 115 g kg −1 by Kidane, Sørheim, Eik, and Steinshamn (2015).…”
Section: Crude Proteinmentioning
confidence: 99%
“…The ranges of both NDF and ADF in genotypes used in our study were higher than values reported by Piluzza et al (2014), which could be attributed to differences of growth stages of measured samples between the two experiments. Labreveux et al (2006) noted that the average NDF of cultivars ranged from 300-400 g kg −1 . In research by Holden et al (2000), NDF concentration was 175 g kg −1 and 250 g kg −1 , and ADF concentration of chicory was 161 g kg −1 and 212 g kg −1 in 2 yr of the experiment.…”
Section: Neutral Detergent Fiber and Acid Detergent Fibermentioning
confidence: 99%